2000
DOI: 10.1046/j.1365-2362.2000.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of homocysteine, cystathionine and methylmalonic acid measurement for diagnosis of vitamin deficiency in high‐aged subjects

Abstract: The metabolites HCY, MMA and CYS are sensitive indicators diagnosing impaired remethylation of homocysteine to methionine with parallel activation of catabolic pathway. Compared to mere HCY or B-vitamins in serum, the efficiency of diagnosing a disturbed HCY metabolism increases very much in utilising the metabolites HCY, MMA and CYS. For differential diagnosis, parallel measurement of folate and creatinine is recommended. The early and correct diagnosis of B-vitamin deficiency in elderly subjects is of high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 42 publications
4
51
0
4
Order By: Relevance
“…Table 3 of the present study indicate that some elderly respondents with raised MMA levels also have abnormal plasma urea and creatinine concentration, and therefore impaired kidney function. Many other studies have also detected a link between raised blood MMA levels and impaired kidney function (Stabler et al, 1986;Rasmussen et al, 1990a, b;Joosten et al, 1993;Lindenbaum et al, 1994;Koehler et al, 1996;Norman, 1998Norman, , 1999van Asselt et al, 1998;Herrmann et al, 2000;Hvas et al, 2000). According to Whitehead et al (1994), the 97.5th centile of plasma creatinine in adults aged 25 -55 y is approximately 122 mmol=l (males) and 100 mmol=l (females), and for plasma urea it is 7.6 mmol=l (males) and 6.8 mmol=l (females).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Table 3 of the present study indicate that some elderly respondents with raised MMA levels also have abnormal plasma urea and creatinine concentration, and therefore impaired kidney function. Many other studies have also detected a link between raised blood MMA levels and impaired kidney function (Stabler et al, 1986;Rasmussen et al, 1990a, b;Joosten et al, 1993;Lindenbaum et al, 1994;Koehler et al, 1996;Norman, 1998Norman, , 1999van Asselt et al, 1998;Herrmann et al, 2000;Hvas et al, 2000). According to Whitehead et al (1994), the 97.5th centile of plasma creatinine in adults aged 25 -55 y is approximately 122 mmol=l (males) and 100 mmol=l (females), and for plasma urea it is 7.6 mmol=l (males) and 6.8 mmol=l (females).…”
Section: Discussionmentioning
confidence: 97%
“…Following the early studies that demonstrated the basic relationship between vitamin B 12 and MMA in man (Gompertz et al, 1967;Chanarin et al, 1973;Norman et al, 1982;Carmel, 2000), and which established reliable assay techniques for MMA (Stabler et al, 1986), were a number of key studies showing a surprisingly high prevalence of raised MMA levels in the plasma of older people, where it appeared to provide a more reliable indicator of functional vitamin B 12 status than serum or plasma vitamin B 12 concentrations per se (Lindenbaum et al, 1988;Rasmussen et al, 1989;Moelby et al, 1990;Joosten et al, 1993;Allen & Casterline, 1994;Lindenbaum et al, 1994;Koehler et al, 1996;Baik & Russell, 1999;Bjorkegren & Svardsudd, 1999;Herrmann et al, 2000). Clearly, the ageing process in itself, and the increasing prevalence of age-related medical conditions that impair vitamin B 12 absorption, both increase the probability that people will become vitamin B 12 -deficient as they grow older.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was based on the assumption that the previously reported lack of association with prognosis might be due to the low sensitivity for total vitamin B 12 as a measure of vitamin B 12 status, making it a poor screening test for deficiency (Naurath et al, 1995;Herrmann et al, 2000Herrmann et al, , 2003Herrmann et al, , 2005. Over the years different serum markers, isolated and in combination, have been evaluated trying to obtain an optimal screening test for deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of the functional markers of vitamin B12 status tHcy, MMA and Cys were measured using gas-chromatography-mass-spectrometry (GCMS) as described elsewhere (26). Serum concentrations of folate were measured with a commercial, competitive chemiluminescence immunoassay (Bayer Diagnostics, Fernwald, Germany) using an ACS Centaur automated analyzer (Bayer Diagnostics, Fernwald, Germany).…”
Section: Subjects and Study Designmentioning
confidence: 99%